nt Insight, 12(1): 79-97 79 ANALISIS KEMAMPUAN KERJA SEBAGAI VALUE DARI PENDIDIKAAN DAN PELATIHAN (Studi Pada Kantor Badan Kepegawaian Daerah Provinsi Bengkulu) - Slamet Widodo; Effed Darta Hadi (Unib Press Universitas Bengkulu, 2017)
The purpose of this study is to determine the role of job training to improve knowledge, skills, attitudes and personality in carrying out the functions and responsibilities toward the achievement of organizational goals. The method used in this study is a survey by conducting in depth-interviews to the employees of the Regional Personnel Board of Bengkulu Province. The results of this study indicate that in particular training or training that has been followed by employees can improve knowledge, work skills, and understanding of their work. This is shown in the way the work and how to solve problems effectively that can be done by employees. Practically the results of this study revealed that an organization needs human resources that have a good individual capacity such as knowledge, skills and understanding in the work. The education and training programs followed by employees are believed to have benefited from individual capacity building and capability, thereby impacting on the quality of services provided.